Modelling Tsunami Based On History In North Of Buru Island, Molluccas - Noya, Yunita A.; Ratuluhain, Eva S.; Sampe, Nadia (Prodi Ilmu Kelautan Fakultas Perikanan dan Ilmu Kelautan Universitas Pattimura, 2023)
The existence of the islands in Maluku is very vulnerable to the danger of a tsunami-generating earthquake, because of their location to faults or faults. The purpose of this study was to analyze the height and propagation time of the tsunami waves in coastal areas in Maluku such as Buru Island, Ambelau Island, Manipa Island, Kelang Island. One of the historical tsunami events in Maluku on January 28, 2004, with a magnitude 6.6 earthquake with a depth of 16.8 km, is a case study parameter for create a tsunami wave propagation model for the purposes of tsunami disaster mitigation in affected coastal areas. The tsunami propagation model in this study uses SitProS modeling to analyze the height and propagation of tsunami waves on the coasts of the islands in Maluku. The bathymetry data used was obtained from the ETOPO site, while the fault parameters were obtained from the BMKG site where the sizes of the strike, dip and slip angles were 194o, 84o and -136o respectively. The result of modeled tsunami height ranges from 0.09 – 0.3 meters with a propagation time up to 13 meters on Ambon Island. Buru Island is an area which close to the epicenter of the earthquake so the waves arrived in the 3rd minute with the maximum height until 0.3 meters.